On recoverying the surface geometry of temple superstructures - Datta, Sambit (TVB School of Habitat Studies, 2005)
The application of computational techniques to the analysis of heritage artifacts enables scholars to bring together diverse fragments of surviving evidence, construe "best-fit" strategies and unearth implicit or hidden relationships. This paper reports a hybrid approach for recovering the surface geometry of temples. The approach combines physical measurements, architectural photogrammetry and generative rules to create a parametric model of the surface. The computing of surface geometry is broken into three parts, a global model governing the overall form of the superstructure, local models governing the geometry of individual motifs and finally the global and local models are combined into a single geometry. In this paper, the technique for recovering surface geometry is applied to a tenth century stone superstructure: the temple of Ranakdevi at Wadhwan in Western India. The global model of the superstructure and the local model of one individual motif are presented.